STUDI KERAGAMAN POLA PITA DNA DAN KESERAGAMAN POPULASI KELAPA GENJAH SALAK (GSK) BERDASARKAN PENANDA RAPD - Hengky, Novarianto; Runtunuwu, Semuel D.; Lengkong, Edy F.; Singkoh, Merlyn (Universitas Sam Ratulangi, 2007)
ABSTRACT Novarianto, H., et.al. 2007. The Study of the Variety of DNA Tape Form and the Coconut Genjah Salak Population Variety Based on RAPD Code. Eugenia 13 (1):109-118. Â The goal of this research to study the variety of DNA tape form and the population variety of coconut Genjah Salak (GSK) based on RAPD code (Randomly Amplified Polymorphic DNA). 25 trees individu of coconut GSK was amplification the genomic of DNA using 35 primer Operon Kit A and Kit B. The coconut GSK individu tree that were analyse was selected based on the female flower production, with average above 40 female flower. The electrophoresis of DNA result of amplication PCR get tape form monomorfic and polimorfic between 25 individu coconut GSK trees that was analyzed. OPA 09 primer and OPB 06 get the result of monomorfic tape form, other wise the OPA 13 primer, OPB 05 and OPB 10 get polimorfic tape form. The genetic similarity in coconut Genjah Salak (GSK) population based on RAPD code rate was 88 % or have the variety genetic of 12 %. Therefore based of this similarity the coconut GSK population was clustering in five groups. The goal of this research to study the variety of DNA tape form and the population variety of coconut Genjah Salak (GSK) based on RAPD code (Randomly Amplified Polymorphic DNA). 25 trees individu of coconut GSK was amplification the genomic of DNA using 35 primer Operon Kit A and Kit B. The coconut GSK individu tree that were analyse was selected based on the female flower production, with average above 40 female flower. The electrophoresis of DNA result of amplification PCR get tape form monomorfic and polimorfic between 25 individu coconut GSK trees that was analyzed. OPA 09 primer and OPB 06 get the result of monomorfic tape form, other the OPA 13 primer, OPB 05 and OPB 10 get polimorfic tape form. The genetic similarity in coconut Genjah Salak (GSK) population based on RAPD code rate was 88 % or have the variety genetic of 12%. Therefore based of this similarity the coconut GSK population was clustering in five groups. Keywords: Keragaman genetic; kelapa Genjah Salak (GSK), Randomly Amplified Polymorphic DNA (RAPD)